On a Colonial Education - ሎ. ኮ. (Universidade de Lisboa, 2021)
In its most common forms around the world, higher education is an enculturation process that perpetuates colonial attitudes, hierarchies, institutions and logics. Based upon perspectives from beyond the Euro-West, this article offers a critical assessment of this systematic entrenchment. Following an analysis of the crafting and experiences of higher education, an exploration of the impacts of implicit and explicit dehumanization, discrimination, oppression and privilege are explored. Drawing entirely upon traditions that have largely been excluded from textbooks and required reading lists of higher education institutions, radical directions are reflected upon, which point toward new horizons. These futures do not focus on de-centring the Euro-West per se, but rather upon cultivating processes of (re)becoming ourselves, within our own cultures and traditions.